PAKAIAN SYAR’I, MEDIA DAN KONSTRUKSI KESALEHAN PEREMPUAN - Nurul Afifah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2018)
One of the themes that are often sought after by Muslim women on social media is the syar'i clothing. It aims to find clothes that are in accordance with the shari'ah of Religion. On the contrary, the production of syar'i clothing on social media is increasing. This study would like to look further at how media discourse attracts attention and constructs women's understandings of the syar'i clothing. This study use the discourse analysis approach by Ernesto Laclau and Chantal Mouffe – with stages: exploration, identification, classification and interpretation. The results of this study are (1) the syar'i clothing discourse on social media is one form of social phenomena in society that is in the form of the emergence of a movement from a particular group in the State of Indonesia (2) basically that discourse is hegemony to clothing not syar'i. (3) the discourses also show the existence of certain motives from the pro syar'i group, namely in the form of realizing and demanding equality and recognition as the cultures of Indonesian society which already existed and were known in Indonesian society.Salah satu tema yang sering diminati oleh wanita muslim di media sosial adalah Pakaian Syar’i. Hal ini bertujuan mencari pakaian yang sesuai dengan syari’at Agama. Sebaliknya, produksi Pakaian Syar’i di media sosial pun semakin meningkat. Kajian ini ingin melihat lebih jauh bagaimana wacana media menarik perhatian dan mengkonstruk pemahaman-pemahaman wanita tentang Pakaian Syar’i. Kajian ini menggunakan pendekatan analisis wacana Ernesto Laclau dan Chantal Mouffe – dengan Tahapan; eksplorasi, identifikasi, klasifikasi dan interpretasi. Hasil dari kajian ini adalah (1) wacana Pakaian Syar’i di media sosial adalah salah satu bentuk fenomena sosial di masyarakat yakni berupa munculnya sebuah gerakan dari kelompok tertentu di Negara Indonesia (2) pada dasarnya wacana-wacana tersebut merupakan bentuk hegemoni terhadap pakaian-pakaian yang dianggap tidak syar’i. (3) wacana-wacana itu juga menunjukkan adanya motif-motif tertentu dari kelompok pro syar’i yakni berupa mewujudkan dan menuntut kesetaraan dan pengakuan selayaknya budaya-budaya masyarakat Indonesia yang sudah lebih dulu ada dan dikenal di masyarakat Indonesia.